A hierarchical two-step floating catchment area analysis for high-tier hospital accessibility in an urban agglomeration region. (June 2022) - Li, Chuanyao; Wang, Junren
Abstract: The medical facility is one of the essential public service facilities. Its spatial accessibility is an important indicator to measure the convenience of access to medical services and a significant factor affecting urban development and the living standards of residents. With the constant process of urbanization, urban agglomerations are formed and developing rapidly. The high-tier healthcare facilities in an urban agglomeration no longer only serve a single city but multiple connected cities. How to characterize healthcare accessibility and supply-demand relationships between medical resources and residents in the context of the urban agglomeration is worthy of being studied but still not fully involved in existing researches. To fill this gap, based on the conventional enhanced two-step floating catchment area method (E2SFCA) and considering the regional development discrepancy and medical preference of residents in the urban agglomeration, this paper proposes a new hierarchical two-step floating catchment area method (H2SFCA) to analyze accessibility to medical facilities. The applicability of the newly proposed method is demonstrated with reference to the Changsha-Zhuzhou-Xiangtan urban agglomeration case. The research findings suggest that: 1) A new method to evaluate accessibility to high-level medical facilities in the urban agglomeration is needed; 2) Due to the ignorance of intensive competition between potential demands, the healthcare accessibility in the core city is overestimated; 3) Residents' medical preference has various impacts on healthcare accessibility in different regions. Highlights: Based on the region hierarchy, a hierarchical 2SFCA is proposed in the context of the urban agglomeration. Accessibility to high tier medical institutions is evaluated in the Changsha-Zhuzhou-Xiangtan urban agglomeration. Comparative analysis is done between conventional enhanced 2SFCA and newly proposed model. Affecting factors on healthcare accessibility in the urban agglomeration are analyzed.